ARDUINO BASED AUTONOMOUS FIRE FIGHTING ROBOT - NARAYANA, Dr.V.A; B.ARCHANA,; RAM, B.SURESH; AKHIL, K.; BALLA, RISHI (The journal of contemporary issues in business and government, 2022)
There are many possibilities a fire can start in an industrial area or in any remote area. For example, in textile mills, gas storages, etc., electric leakages can lead to huge damage. Also, it’s a worst-case scenario, causing heavy losses not only financially but it also can destroy areas surrounding it. Robots can protect human lives and their wealth and surroundings. The aim is to design a “AURDINO BASED AUTONOMOUS FIRE FIGHTING ROBOT” using embedded system. A robot is capable of fighting and helps in extinguishing fire. It must be able to autonomously navigate through floor plan while actively scanning for a flame. The robot can even act as a path guider in normal case and can act as a fire extinguisher in emergency. Robots designed to find a flame, before it reaches out ofcontrol, can one day work with fire-fighters greatly reducing the risk of injury to victims. The project will help in generating innovations in the fields of robotics while working towards a practical and obtainable solution to save lives and to reduce the risk of property damage.With the development in the field of robotics, human intrusion has become less and robots are being widely used for safety purpose. In our day-to-day lives,fire accidents have become common and sometimes may lead to hazards that make it hard for the firemen to protect human life. In such cases, a fire fighting robot is used to guard human lives, wealth and surroundings from fire accidents.